Appropriating the returns of patent statistics: Take-up and development in the wake of Zvi Griliches - Mendonça, S.; Confraria, H.; Godinho, M.M. (Appropriating the returns of patent statistics: Take-up and development in the wake of Zvi Griliches, 2021)
Three decades after the publication of Zvi Griliches’ (1990) influential survey on “Patent statistics as economic indicators”, the uses and limitations of patent statistics remain a core issue in the field of innovation studies. This paper follows through Griliches’ seminal work to understand how the literature using patents as an empirical resource developed over time. How has this indicator been adopted and how has it been adapted to different research challenges? We address this question by examining the citation tree of nearly 2000 articles published in almost 400 journals found to refer to Griliches’ seminal contribution between 1990 and 2019. We combine bibliometric techniques and qualitative analysis to provide a close-up moving picture of patents as a data resource: growth and variety of usage, impact on disciplines and journals, driving institutions and geographies, major topics and research issues. We find that five main themes emerge: 1) Economic growth; 2) Geography of innovation; 3) Innovation management/performance; 4) Pat-methods; and 5) Green innovation. Shouldered by these findings, we discuss potential pathways for future patent-based research.